2016
DOI: 10.1002/chem.201604473
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of an 18F‐Labeled Hydrocyanine Dye as a Multimodal Probe for Reactive Oxygen Species

Abstract: Hydrocyanine dyes are sensitive "turn-on" type optical probes that can detect reactive oxygen species (ROS). We have developed a method to prepare an F-labeled hydrocyanine dye as a multi-modal PET and optical "turn-on" probe. A commercially available near infrared (NIR) dye was modified with a fluorinated prosthetic group that did not alter its ROS sensing properties in the presence of superoxide and hydroxyl radicals. The F-labeled analogue was produced using a single-step terminal fluorination procedure. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 89 publications
(53 reference statements)
0
47
0
2
Order By: Relevance
“…These studies are promising, because the tracers showed ROS‐specific uptake in vitro and in vivo using an animal model of neuroinflammation. Moreover, Carroll et al reported a prodrug construct that releases the PET tracer 3′‐deoxy‐3′‐[ 18 F]fluorothymidine ([ 18 F]FLT) when reacting with ROS, and, more recently, a hydrocyanine dye has been reported allowing multimodal PET and optical imaging . However, the imaging of ROS activity in vivo in tumours has not yet been reported extensively.…”
Section: Introductionmentioning
confidence: 99%
“…These studies are promising, because the tracers showed ROS‐specific uptake in vitro and in vivo using an animal model of neuroinflammation. Moreover, Carroll et al reported a prodrug construct that releases the PET tracer 3′‐deoxy‐3′‐[ 18 F]fluorothymidine ([ 18 F]FLT) when reacting with ROS, and, more recently, a hydrocyanine dye has been reported allowing multimodal PET and optical imaging . However, the imaging of ROS activity in vivo in tumours has not yet been reported extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Al‐Karmi, et al. also sought to radiofluorinate the Cy7 hydrocyanine dye, though for use as a PET coupled on‐off optical probe which would fluoresce in the presence of reactive oxygen species (ROS) [46] . An initial two‐step radiosynthesis of the compound involved nucleophilic aromatic substitution of a nitro‐substituted precursor ( 29 ) using [ 18 F]fluoride with a Kryptofix 222 phase transfer catalyst in DMF, followed by reduction of the iminium salt using sodium borohydride, as shown in Figure 15.…”
Section: Fluorine‐18 Labelled Cyanine Dyesmentioning
confidence: 99%
“… Cy7 dye with a 2‐[ 18 F]fluoropyridine prosthetic group for the PET imaging and on‐off optical sensing of ROS [46] . Initial syntheses starting from 29 involved a multistep radiofluorination and reduction reaction which afforded 31 in only 19 % RCY.…”
Section: Fluorine‐18 Labelled Cyanine Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…[286] Weitere,auf ROS reagierende PET-Reagenzien haben Wilson, Va lliant et al verçffentlicht. [287,288] Renslo,E vans und Mitarbeiter synthetisierten PET-Sonden, um labile Eisenreservoirs in lebenden Tieren zu verfolgen, die bei der Bildgebung systemische Veränderungen der Eisenverfügbarkeit in spontanen Tu moren in Mäusen und in vivo aufdecken. Die Tu moren gehen auf ein molekularbiologisch etabliertes Prostatakrebsmodell durch den Verlust der Phosphatase PTEN (phosphatase and tensin homolog) zurück (Abbildung 7c).…”
Section: Aufsätzeunclassified